Arab Pra-Islam (Sistem Politik Dan Kemasyarakatan Sistem Kepercayaan Dan Kebudayaan) - Anjar Fikri Haikal; Mahmudah Mahmudah; Kholid Mawardi (Journal on Education, 2023)
Jahiliyah is a term given to Arab society that refers to the period of time and conditions in Arab lands before the arrival of Islam in 610 AD. The word jahiliyah is translated as "Age of Ignorance". The term jahiliyah comes from the verb jahiliya "to be stupid or stupid, to act stupid". In modern times, various Islamic scholars have used the term to denounce what they see as the un-Islamic nature of social and private life in the Muslim world. MethodQualitative research is research that holistically intends to understand the phenomenon of what is experienced by the research subject, be it behavior, perception, motivation or action, and descriptively in the form of words and language, in a special natural context and by utilizing various methods. natural.". Library research or literature study has several characteristics, namely. Result in artickel In terms of the religion adopted by the Arabs before the arrival of Islam, there were several beliefs that they adhered to, namely: Fatalism, Paganism, belief in Allah as the super God and Monotheism. In terms of culture, the Arab nation has long been known as a nation of poetry lovers. They created a wide variety of poetry, poetry and prose. From a social point of view, the Arab nation has that solidarity among fellow members of one tribe is very strong, while this feeling with the tribe does not exist at all. The political and social life of pre-Islamic Arab society, both nomadic and sedentary, lived in Bedouin tribal culture.